NILAI SIKAP DAN KARAKTER DALAM PERIBAHASA INGGRIS SEHUBUNGAN DENGAN SAPI - Mirahayuni, N.K.; Garnida, Susie Chrismalia (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2016)
This paper discusses social wisdom, values and attitudes expressed in English proverbs related to cow. This paper is a part of an ongoing study on values in English and Indonesian proverbs related with horse, cow, bufallo and donkey. Proverbs are generally identified from its brief and memorable words or sentences that express truth and reality and in many ocassions express advice reflected from daily experiences and general observation that are expressed in a fixed and effective language forms that they are memorable and are ready to use as an effective rhetorical device in both oral and written language (Mieder, 2004). Proverbs express an awareness of human condition and weakness that voices of advice that are expressed in this special language may be sounded with clarity, humour, wit and insights (Barajaz, 2010). The paper reports the descriptive qualitative study on ninety (90) English proverbs related to cow. The data of the study are collected from various printed and electronic sources of English proverbs. The study found that a number of good wisdom, values and attitudes are taught and transmitted using cow as the keyword such as the value of acquired over inherited social status, discipline and responsibility, hardworking, minimizing trouble, habit formation and others. The study may be useful in the context of English language learning, that English learners may learn the socio-cultural values wrapped in the daily language expressions such as proverbs. Keywords: English proverbs, socio-cultural values